SISTEM NUMERALIA BAHASA NAMLA - Yohanis Sanjoko (Balai Bahasa Provinsi Papua, 2019)
Namla language is a finding of Tim Pemetaan dan Kekerabatan Bahasa-Bahasa Daerah. Namla language found in Namla Villages, Senggi District, Keerom Regency of Papua Province. Numeral is a word or phrase which can show not only number or quantity but also the amount of things or the order in a row. This research used descriptive method by doing in three phases, there are data collecting, analyzing data, and presenting the result of analyzing data. Analyzing data by distributional method is conducted after the selected data was classified. Namla language has fine kinds of numeral, namely cardinal number, ordinal number, collective cardinal number, undefinite cardinal number, and distributive number. In Namla language, the numeral always be after a noun in a phrase.